Heat-shock protein 27 (Hsp27) as a target of methylglyoxal in gastrointestinal cancer - Oya-Ito, Tomoko; Naito, Yuji; Takagi, Tomohisa; Handa, Osamu; Matsui, Hirofumi; Yamada, Masaki; Shima, Keisuke; Yoshikawa, Toshikazu (Biochimica et biophysica acta, 2011)
The molecular mechanisms underlying the posttranslational modification of proteins in gastrointestinal cancer are still unknown. Here, we investigated the role of methylglyoxal modifications in gastrointestinal tumors. Methylglyoxal is a reactive dicarbonyl compound produced from cellular glycolytic intermediates that reacts non-enzymatically with proteins. By using a monoclonal antibody to methylglyoxal-modified proteins, we found that murine heat-shock protein 25 and human heat-shock protein 27 were the major adducted proteins in rat gastric carcinoma mucosal cell line and human colon cancer cell line, respectively. Furthermore, we found that heat-shock protein 27 was modified by methylglyoxal in ascending colon and rectum of patients with cancer. However, methylglyoxal-modified heat-shock protein 25/heat-shock protein 27 was not detected in non cancerous cell lines or in normal subject. Matrix-associated laser desorption/ionization mass spectrometry/mass spectrometry analysis of peptide fragments identified Arg-75, Arg-79, Arg-89, Arg-94, Arg-127, Arg-136, Arg-140, Arg-188, and Lys-123 as methylglyoxal modification sites in heat-shock protein 27 and in phosphorylated heat-shock protein 27. The transfer of methylglyoxal-modified heat-shock protein 27 into rat intestinal epithelial cell line RIE was even more effective in preventing apoptotic cell death than that of native control heat-shock protein 27. Furthermore, methylglyoxal modification of heat-shock protein 27 protected the cells against both the hydrogen peroxide- and cytochrome c-mediated caspase activation, and the hydrogen peroxide-induced production of intracellular reactive oxygen species. The levels of lactate converted from methylglyoxal were increased in carcinoma mucosal cell lines. Our results suggest that posttranslational modification of heat-shock protein 27 by methylglyoxal may have important implications for epithelial cell injury in gastrointestinal cancer. ► Hsp25/Hsp27 is modified by methylglyoxal in carcinoma but not in healthy cell lines. ► Methylglyoxal modification of Hsp27 was necessary for its enhanced anti-apoptotic effects. ► Methylglyoxal modification of Hsp27 decreases intracellular reactive oxygen species. ► Lactate converted from methylglyoxal are elevated in carcinoma mucosal cell lines.